Proceedings of the 2014 Conference on Internet Measurement Conference 2014
DOI: 10.1145/2663716.2663756
|View full text |Cite
|
Sign up to set email alerts
|

Back-Office Web Traffic on The Internet

Abstract: Although traffic between Web servers and Web browsers is readily apparent to many knowledgeable end users, fewer are aware of the extent of server-to-server Web traffic carried over the public Internet. We refer to the former class of traffic as front-office Internet Web traffic and the latter as back-office Internet Web traffic (or just front-office and back-office traffic, for short). Back-office traffic, which may or may not be triggered by end-user activity, is essential for today's Web as it supports a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Large companies that generate and deliver content like Google [24,32,77], Facebook [65], Microsoft [10], Amazon [11], and Netix [50] created their own CDNs. This approach allows them to customize and to optimize content delivery for their needs and assets [36,45,60,68]. Given the scale at which they operate, it can also reduce their costs.…”
Section: Introductionmentioning
confidence: 99%
“…Large companies that generate and deliver content like Google [24,32,77], Facebook [65], Microsoft [10], Amazon [11], and Netix [50] created their own CDNs. This approach allows them to customize and to optimize content delivery for their needs and assets [36,45,60,68]. Given the scale at which they operate, it can also reduce their costs.…”
Section: Introductionmentioning
confidence: 99%
“…This can be a blessing if these installations can improve end user performance. For example, it has been reported that round trip times between end-users and these servers can be even less than a millisecond [86,104]. Such low delays are a step towards addressing the future requirements and a way for Hypergiants like Google and Facebook to play an important role in future services, including 5G.…”
Section: Discussionmentioning
confidence: 99%
“…The extended serving infrastructure can also better deal with increased traffic, e.g., during the COVID-19 pandemic [43], as was reported recently by Google [56] and Akamai [70]. At the same time, these deployments mean that a substantial fraction of traffic demand can be served locally without crossing inter-domain links or private interconnections [81,86,90,111,113,114]. This "zero AS-hop" Internet has regulatory implications.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we call this address the client-facing IP, and the other address we call the operations IP. The operations IP is used solely for CDN-internal communication [29]. The distinction between these two addresses that is relevant for this study is that the operations IP is never exposed in replies to forward DNS queries.…”
Section: Data Collection and Samplingmentioning
confidence: 99%